A new data hiding algorithm based on minesweeper game for binary images - Tuncer, Turker; Avci, Derya; Avci, Engin (Gazi Univ, Fac Engineering Architecture, 2016)
Nowadays, a lot of data hiding algorithms for binary images have been proposed in the literature. The main purpose of these algorithms is to provide data hiding with high capacity and high visual quality. The pattern based data hiding algorithms are commonly used to achieve this purpose. In this paper, a new data hiding algorithm is suggested. This algorithm is based on minesweeper game for binary images. Neighborhood degree is calculated by selecting mine value as 0 or 1. The size of 3x3 non overlapping blocks have been used to determine neighborhood degree. Data hiding process is implemented by modifying the obtained neighborhood degree. Hamming distance is calculated to keep distortion in minimum level. In the selection of similar blocks with different neighborhood degrees, privacy of the algorithm is provided by using random number generators. The experimental results showed that the proposed data hiding algorithm resulted successfully.
Ikili imgeler için mayin tarlasi oyunu tabanli yeni bir veri gizleme algoritmasi
Keywords: Binary image; data hiding; minesweeper game; digital watermarking; steganography; information security